The roAp Stars Observed by the Kepler Space Telescope - Holdsworth, Daniel L. (Frontiers in Astronomy and Space Sciences, 2021)
Before the launch of the Kepler Space Telescope, most studies of the rapidly oscillating Ap (roAp) stars were conducted with ground-based photometric B observations, supplemented with high-resolution time-resolved spectroscopy and some space observations with the WIRE, MOST and BRITE satellites. These modes of observation often only provided information on a single star at a time, however, Kepler provided the opportunity to observe hundreds of thousands of stars simultaneously. Over the duration of the primary 4-yr Kepler mission, and its 4-yr reconfigured K2 mission, the telescope observed at least 14 new and known roAp stars. This paper provides a summary the results of these observations, including a first look at the entire data sets, and provides a look forward to NASA's TESS mission.